Exploring drive for thinness as a perfectionistic strategy to escape from shame experiences - Ferreira, C. (2015)
Ferreira, C., Trindade, I. A., & Ornelas, L. (2015). Exploring drive for thinness as a perfectionistic strategy to escape from shame experiences Spanish Journal of Psychology, 18(29), 1–7. doi:10.1017/sjp.2015.27